Efektifitas Ekstrak Daun Mayana (Solenostemon Scutellarioides (L)) Terhadap Uji Fisik Organoleptik Daging Babi - Aloysia Tenny Damayanti Indriastuti; Irine Ike Praptiwi; Maria Magdalena Nadu Lesik; Heni Vensye Saiya (AGRICOLA, 2019)
Community needs for animal protein are increasingly increasing. One animal protein that can be developed and commonly farmed in local Papuan communities today is pigs. Pork has the disadvantage of high fat content, making pork is not widely consumed by the public. Additional materials that are often used by the community,basically aims to improve the taste of food, ut without realizing it, the additional material actually has another effect, both negative effects and positive effects. One additional ingredient that can be used as a mixture in pork is mayana leaf (Solenostemon scutellarioides (L)), but has not been scientifically studied, how the influence of the leaves of mayana (Solenostemon scutellarioides (L)) on the quality of pork. This study aims to determine the effectiveness of mayana leaf extract on the organoleptic physical test of pork through the boiling method. This study used a complete randomized design with 3 treatments and 3 replications, treatment including the use of mayana leaves (Solenostemon scutellarioides (L)) 0%, 20% and 40%. The parameters observed included cooking losses, and organoleptic tests including color, taste, texture, aroma, acceptability. The results showed that boiling using mayana leaf extract did not have a significant effect on cooking losses in pork. In organoleptic tests, boiling using extracts and mayana have a very significant effect. With the highest value for A3 treatment color of 3.65. The taste in A2 treatment was 3.21. Texture and aroma in the treatment of A3, with the highest value for texture 3.77 and aroma 4.00